Comparison of temperature dependent deformation mechanisms of 8YSZ thermal barrier coatings prepared by air-plasma-spray and D-gun thermal spray: An in situ study. Issue 10 (August 2019) - Cho, Jaehun; Li, Jin; Shang, Z.; Lopez, Jack M.; Jarosinski, William J.; Gentleman, M.M.; Viswanathan, Vaishak; Xue, S.; Wang, H.; Zhang, X.
Abstract: 8 weight percent yttria stabilized zirconia (8YSZ) has gained widespread use in thermal barrier coatings for the hot sections of aero and power generation turbines due to its superb thermal and mechanical properties. In this study, in situ microcompression tests were conducted to evaluate the mechanical performance of 8YSZ coatings with dense vertically cracked (DVC) microstructures produced by detonation gun thermal spray to those deposited by air plasma spray (APS). At room temperature, the APS coatings showed high variability in fracture strength resulting from cracks and pores in the coating. DVC coatings, conversely, exhibited fracture strengths ranging from 3.9 to 6.6 GPa and less variability in fracture strength attributed to the relatively dense and less defective microstructure. At 500 °C, both coatings showed better consistency of fracture strength and enhanced deformability owing to deformable pores, ferroelastic domain switching, and dislocation activities.